Pengaruh Kualitas Layanan, Persepsi Harga Dan Cita Rasa Terhadap Loyalitas Pelanggan Pada Toko Oleh-Oleh Insyira Pekanbaru - Ramadhani, Nurvadea; Rachmad, Ferizal (Basecamp Economics PubMed, 2024)
This research was conducted on Customers at Insyira Pekanbaru Gift Shop. The purpose of this study was to analyze the effect of service quality, price perception and taste on customer loyalty at Insyira Pekanbaru souvenir shop. Data collection techniques using a questionnaire. The type used in this research is a quantitative type of influence between variables. The population in this study were 96 customers at the Insyira Pekanbaru By-Pass Shop using purposive sampling method. Data analysis used in this study was quantitative with multiple linear regression methods. Based on the results of this study indicate that Service Quality, Price Perception and Taste have an effect on Customer Loyalty both partially and simultaneously. The results of the Coefficient of Determination (R2) show that the magnitude of the influence of the two independent variables together on the dependent variable is 60.5%, while the remaining 39.5% is another variable not examined in this study. Translated with DeepL.com (free version)